2016
DOI: 10.1016/j.celrep.2016.08.045
|View full text |Cite
|
Sign up to set email alerts
|

COOLAIR Antisense RNAs Form Evolutionarily Conserved Elaborate Secondary Structures

Abstract: There is considerable debate about the functionality of long non-coding RNAs (lncRNAs). Lack of sequence conservation has been used to argue against functional relevance. We investigated antisense lncRNAs, called COOLAIR, at the A. thaliana FLC locus and experimentally determined their secondary structure. The major COOLAIR variants are highly structured, organized by exon. The distally polyadenylated transcript has a complex multi-domain structure, altered by a single non-coding SNP defining a functionally di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
122
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(134 citation statements)
references
References 47 publications
(68 reference statements)
1
122
0
Order By: Relevance
“…These results were reproducible across multiple RNAs and multiple target cell types. Importantly, recent work from numerous laboratories has used various SHAPE reagents in vitro, with results validated by a number of orthogonal techniques (Somarowthu et al 2015;Guo and Bartel 2016;Hawkes et al 2016;Pirakitikulr et al 2016). These published examples and our head-to-head comparison of SHAPE electrophiles provide clear and direct evidence that in vitro the reagents are largely equivalent.…”
Section: Resultsmentioning
confidence: 61%
“…These results were reproducible across multiple RNAs and multiple target cell types. Importantly, recent work from numerous laboratories has used various SHAPE reagents in vitro, with results validated by a number of orthogonal techniques (Somarowthu et al 2015;Guo and Bartel 2016;Hawkes et al 2016;Pirakitikulr et al 2016). These published examples and our head-to-head comparison of SHAPE electrophiles provide clear and direct evidence that in vitro the reagents are largely equivalent.…”
Section: Resultsmentioning
confidence: 61%
“…FLC reduction is associated with induction of long noncoding RNA (lncRNA) transcripts, both sense and antisense to FLC (Kim et al ., ). Antisense COOLAIR is a highly structured molecule (Hawkes et al ., ) that coats and downregulates the FLC locus upon cold exposure (Rosa et al ., ). Sense lncRNA COLDWRAP forms a repressive intragenic chromatin loop, whereas COLDAIR facilitates recruitment of Polycomb Repressive Complex 2 (PRC2) to FLC (Kim & Sung, ; Kim et al ., ).…”
Section: Convergence At Transcriptional Hubsmentioning
confidence: 99%
“…For example, by combining the structures of SHAPE [66], DMS [67] and terbium structure probing [68], it has been shown that Hotair forms intricate structural modules that are essential in binding to PRC2 to carry out its function [69]. Coolair is another lncRNA with a complex structure that includes multi-helix junctions and two right-hand turn motifs, which appear to impact its function [70]. By developing a picture of the partners that interact with lncRNAs, their mechanism of function can be inferred and further tested, through the removal or occlusion of the interacting domains, as revealed by the structure of the lncRNA.…”
Section: Determining the Mechanism Of Lncrna Functionmentioning
confidence: 99%